Pengaruh Program Talent Class Speak Up terhadap Kemampuan Kognitif Peserta Didik Paket B dan Paket C di Homeschooling Kak Seto Surabaya - Putri Intan Permatasari; Rofik Jalal Rosyanafi (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Talent class speak up at Homeschooling Kak Seto Surabaya is a non-academic activity with the aim of developing and training students' English speaking skills. In the talent class speak up learning process, an involvement of students' cognitive abilities is needed to get a change in knowledge. The purpose of this study was to determine whether there was an influence of the talent class speak up program on the cognitive abilities of students in package B and package C pursuit programs. The method used in this research was descriptive quantitative. The results of the study show the value of (5,142) > (2,032) and the value significant 0.000 <0.05. this shows that there is a significant influence of the talent class speak up program on students' cognitive abilities package B and package C at Homeschooling Kak Seto Surabaya. The existence of a talent class speak up program helps students improve their English speaking skills.